Effectiveness of a food literacy and positive feeding practices program for parents of 0 to 5 years olds in Western Australia - Tartaglia, Jennifer; Jancey, Jonine; Scott, Jane Anne; Dhaliwal, Satvinder; Begley, Andrea (Australian Health Promotion Association, 2023)
Issue Addressed: Lifelong eating behaviours are established in childhood. Improving parents' food literacy skills is essential, as parents play a fundamental role in estab lishing their children's healthy eating behaviours and preferences for nutritious food. This paper describes the development and evaluation of an innovative program that combines food literacy with positive parent feeding practices, targeting parents in disadvantaged areas of Western Australia. Methods: The Food Sensations® for Parents five-week program was delivered to par ticipants from community-based parenting organisations during 2020 and 2021. For mative research and a pre-post evaluation design were adopted. Results: Pre- and post-evaluation data were collected from 224 participants (96% female). There was a statistically significant improvement in the mean score for 13 food literacy behaviours, 10 positive parenting feeding practices and a mean increase in parents' daily vegetable intake of 1/3 serve. Participants reported signifi cantly greater net improvements in food literacy behaviours than feeding practices, the largest being the Use a nutrition information panel to make food choices (33.1%). Multivariate logistic regression analyses found English as a first language, being older than 35, and from a higher Socio-Economic Index for Areas resulted in a higher likeli hood of positive changes in behaviours and practices. Conclusions: The findings indicate that the program is effective in improving the fre quency of use of food literacy behaviours, positive parenting feeding practices and increasing vegetable consumption. So What?: Analysing improvements in food literacy behaviours and feeding practices provides clarity on what change can be expected with a five-week parent program.